Edukasi Pembuatan Laporan Keuangan UMKM Kepada UMKM Forsamik di Kelurahan Kutabumi Kabupaten Tangerang - Gultom, David Parningotan; Hendrawan, Yusuf; Herdiansyah, Deni; Syahriyah, Yayah; Apriansyah, Reza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This community service activity is entitled Education for Making MSME Financial Reports to Forsamik MSMEs in Kutabumi Village, Tangerang Regency. The general objective of this community service activity is to provide understanding, training and practical knowledge of accounting that can have an impact on the preparation of simple financial reports for MSME actors. The methods used are survey methods and direct delivery of material as well as simulations and discussions regarding accounting, tariffs, rules and reporting of MSME taxes, financial management, and preparation of simple financial reports. The conclusion of this community service is that it provides knowledge related to the importance of preparing good financial reports for public welfare and the many benefits if MSME actors make good financial reports.